Collapse of tall granular columns in fluid - Kumar Krishna; Soga Kenichi; Delenne Jean-Yves (EPJ Web of Conferences, 2017)
Avalanches, landslides, and debris flows are geophysical hazards, which involve rapid mass movement of granular solids, water, and air as a multi-phase system. In order to describe the mechanism of immersed granular flows, it is important to consider both the dynamics of the solid phase and the role of the ambient fluid. In the present study, the collapse of a granular column in fluid is studied using 2D LBM - DEM. The flow kinematics are compared with the dry and buoyant granular collapse to understand the influence of hydrodynamic forces and lubrication on the run-out. In the case of tall columns, the amount of material destabilised above the failure plane is larger than that of short columns. Therefore, the surface area of the mobilised mass that interacts with the surrounding fluid in tall columns is significantly higher than the short columns. This increase in the area of soil - fluid interaction results in an increase in the formation of turbulent vortices thereby altering the deposit morphology. It is observed that the vortices result in the formation of heaps that significantly affects the distribution of mass in the flow. In order to understand the behaviour of tall columns, the run-out behaviour of a dense granular column with an initial aspect ratio of 6 is studied. The collapse behaviour is analysed for different slope angles: 0°, 2.5°, 5° and 7.5°.